9 The Sigma-1 Receptor Agonist PRE-084 Attenuates Inflammation-Sensitized Nmdar-Mediated Excitotoxic Brain Injury in Newborn Mice. (October 2012) - Posod, A; Neumayer, K; Neubauer, V; Keller, M; Wegleiter, K; Urbanek, M; Kiechl-Kohlendorfer, U; Griesmaier, E
Abstract : Excitotoxicity and inflammation play crucial roles in the etiopathogenesis of perinatal brain injury. We have shown that the sigma-1 receptor agonist 2-(4-morpholinethyl) 1-phenylcyclohexanecarboxylate (PRE-084) protects against N-methyl-d-aspartate (NMDA) receptor-mediated excitotoxic brain injury. In models of adult central nervous system pathology, PRE-084 has demonstrated potent anti-inflammatory properties, which makes it a promising candidate for countering inflammation-enhanced perinatal brain injury. In the present study we evaluated the effect of PRE-084 in a neonatal mouse model of inflammation-sensitized excitotoxic brain injury. From postnatal days 1 to 4, pups were pre-sensitized by intraperitoneal injections of IL-1beta (10ng). Two hours after the last IL-1beta dose, pups received an intracranial ibotenate injection, 1 hour after the insult they were randomly treated with i) 0.1 µg/g bodyweight PRE-084 or ii) vehicle. Administration of PRE-084 resulted in a significant decrease in cortical grey (mean length of the lesion: vehicle 780.00µm ± 495.35 vs. PRE-084 433.33µm±116.51; n=8–9; p<0.05) and adjacent white matter damage (mean length of the lesion: vehicle 767.50µm ± 489.07 vs. PRE-084 391.11µm±126.14; n=8–9; p<0.05). No sex-specific differences in lesion size were detected (n=3–6, p>0.05). PRE-084 treatment significantly reduced the number of isolectin B4-positive activated microglial cells in perilesional white matter (mean number of isolectin B4-positive activated microglia vehicle 36.40±6.96 vs. PRE-084 19.93±11.99; n=5; p<0.05). We are the first to report that PRE-084 reduces inflammation-sensitized NMDAR-mediated excitotoxic perinatal brain damage. Since sigma-1 receptor agonists are investigated in clinical trials in adult neurological diseases, they might be considered a promising therapeutic option also in perinatal brain injury.